Antibacterial Effectiveness Test of Ethanol Extract of Gadung Mango Leaves Against Staphylococcus aureus and Escherichia coli Bacteria - Indira Pipit Miranti; Vivin Andriani (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kuningan, 2024)
Infection is a disease that often occurs in Indonesia. This disease is caused by pathogenic microbes, one of which is bacteria. Staphylococcus aureus and Escherichia coli are bacteria that cause infection. Pharmacological therapy for bacterial infections used to use antibiotics, currently tends to use drugs that come from nature. One of the plants that has the potential as an antibacterial is gadung mango leaves. This study aims to determine the effectiveness of mango leaf ethanol extract against S.aureus and E.coli bacteria. The method used was well diffusion with concentrations of ethanol extract of mango leaves 0.5% (S1), 0.75% (S2), 1% (S3), streptomycin (K+), and ethanol (K-), respectively treatment was repeated 5 times. Data that can be analyzed using One Way ANOVA with a significant level of 0.05. Based on the results of the antibacterial extract of ethanol extract of mango gadung leaves, it has the potential to be better on E. coli bacteria, namely at a concentration of 1% (S3) of 16.05 mm, whereas on S.aureus K+ bacteria (Streptomycin) it is better on control + of 15.9 mm.